2014
DOI: 10.1128/mcb.00796-14
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Tm5NM1 Spatially Restricts Src Kinase Activity through Perturbation of Rab11 Vesicle Trafficking

Abstract: dIn order for cells to stop moving, they must synchronously stabilize actin filaments and their associated focal adhesions. How these two structures are coordinated in time and space is not known. We show here that the actin association protein Tm5NM1, which induces stable actin filaments, concurrently suppresses the trafficking of focal-adhesion-regulatory molecules. Using combinations of fluorescent biosensors and fluorescence recovery after photobleaching (FRAP), we demonstrate that Tm5NM1 reduces the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Rab11 has been shown to function in the movement of recycled endosomes to the membrane and regulates epithelial cell polarity [32,33]. It has also been reported to participate in cellular functions and cancerous metastasis [29,[34][35][36][37][38][39]. Our previous work further demonstrated that Rab11 can regulate E-cadherin expression during cell transformation in colon cancer [19].…”
Section: Introductionmentioning
confidence: 69%
“…Rab11 has been shown to function in the movement of recycled endosomes to the membrane and regulates epithelial cell polarity [32,33]. It has also been reported to participate in cellular functions and cancerous metastasis [29,[34][35][36][37][38][39]. Our previous work further demonstrated that Rab11 can regulate E-cadherin expression during cell transformation in colon cancer [19].…”
Section: Introductionmentioning
confidence: 69%
“…Proteins were extracted as previously described (Bach et al, ). Protein concentrations were equalised following quantification with the Biocinchoninic acid (BCA) Protein Assay Kit (Pierce Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Their major function is to regulate the dynamics of the associated actin filament, via regulating access of different myosin motors (Bryce et al, ; Clayton et al, ; Manstein, & Mulvihilll, ; Schevzov et al, ). Tpm3.1 stabilises actin filaments, through myosin II recruitment (Bryce et al, ; Clayton, Pollard, Murray, & Lord, 2015; Gateva et al, ; Schevzov et al, ) and this stabilising function underpins the multiplicity of roles that have been ascribed to this ubiquitously expressed protein (Bach et al, 2009; ; Bryce et al, ; Caldwell et al, ; Clayton et al, ; Lees, Bach, Bradbury, Lees et al, , 2013; Lim et al, ; Schevzov et al, ; Vlahovich et al, ). Elevated Tpm3.1 expression inhibits both 2‐dimensional (2D) and 3D single cell migration (Bach et al, 2009; ; Bryce et al, ; Lees, Bach, Bradbury, Lees et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, RCP/Rab11-driven recycling of ␣5␤1-integrin controls the activation of Rac and RhoA in different cell lines (A2780, MDA-MB-231 and HT1080 cells) (Jacquemet et al, 2013). The recycling of ␤1-integrin is known to be regulated by Arf6 and Rab11 (Eva et al, 2010(Eva et al, , 2012Powelka et al, 2004) and Rab11 was also implied in the targeted delivery of Src tyrosine kinases to FAs (Bach et al, 2014) where Src contributes to the phosphorylation of FAK (Canel et al, 2013). In addition, ␤1-integrin recruitment can lead to an activation of Rac1 in HeLa cells (O'Toole et al, 2011).…”
Section: Influence Of Reggie On Fak Rac1 and Rab11 Activationmentioning
confidence: 99%